KARAKTERISTIK TEPUNG JAGUNG TERMODIFIKASI MELALUI PROSES FERMENTASI SPONTAN, MENGGUNAKAN Lactobacillus casei DAN RAGI TAPE - Lintang Aprilliani; Nur Aini; Gunawan Wijonarko; Budiyanto Budiyanto (Faculty of Agricultural Technology, University of Jember, 2013)
In order to take advantage of commodity diversification with the local non-wheat flour processing can be used to substitute the manufacture of food products in order to overcome the dependency on flour. One of the local commodity that can be processed into flour is corn. Cornmeal likely replace wheat flour in the manufacture of a wide range of processed products such as bread and biscuits Cockies. The study aims to determine the best methods in the manufacture of corn to produce corn starch with physical and chemical properties either through spontaneous fermentation, using Lactobacillus casei fermentation and using tape yeast. Corn used in this study is the heroine of white maize varieties. Statistical analysis showed that the fermentation process effect on ash content, soluble protein content and total protein content of corn flour produced. For the other variables are not affected by the process of fermentation. Best Samples owned by J2L3 sample with the highest soluble protein content of 2.3%, which is fermented using Lactobacillus casei for 3 days.Keywords: maize, white heroine, fermentation, Lactobacillus casei, yeast tape, soluble protein